2019
DOI: 10.7150/thno.35391
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human ESC-derived mesenchymal stem cell spheroids ameliorates spontaneous osteoarthritis in rhesus macaques

Abstract: It has been demonstrated that mesenchymal stem cells (MSCs) differentiated from human embryonic stem cells (hESCs), name EMSCs, can treat a variety of autoimmune and inflammatory diseases, with similar efficacies to those achieved with MSCs derived from somatic tissues such as bone marrow (BMSCs). The chance increases even higher for EMSCs, than somatic tissue derived MSCs​, to become a cell drug as the former can be produced in large scale from an unlimited hESC line with easier quality control and less biosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…The pathological process of OA in these quadrupeds may be quite different from that in humans. One study used a model of OA in primates (rhesus monkeys) [ 60 ]. Encouragingly, the results of this study showed that both xenogenic ESC-derived MSCs (EMSCs) and allogeneic BMSC transplantation had therapeutic effects on knee joint OA in rhesus monkeys, and the results were better than those in the control group.…”
Section: Cartilage Regeneration Strategies Involving Stem Cellsmentioning
confidence: 99%
“…The pathological process of OA in these quadrupeds may be quite different from that in humans. One study used a model of OA in primates (rhesus monkeys) [ 60 ]. Encouragingly, the results of this study showed that both xenogenic ESC-derived MSCs (EMSCs) and allogeneic BMSC transplantation had therapeutic effects on knee joint OA in rhesus monkeys, and the results were better than those in the control group.…”
Section: Cartilage Regeneration Strategies Involving Stem Cellsmentioning
confidence: 99%
“…Indeed, Hwang et al, demonstrated that ESCs expanded in co-culture with chondrocytes resulted in more homogeneous ESC-derived cartilage tissue both in vitro and in vivo [31]. Some studies have generated MSCs derived from ESCs and utilized their exosomes [32] and spheroids [33] in murine and primate OA models. Similarly, exosomes secreted by iPSC-derived MSCs were used in regenerating OA in a rat model [34].…”
Section: Cell-based Treatmentsmentioning
confidence: 99%
“…For chondrogenic differentiation, 2 × 10 5 hUC-MSCs were pelleted in 15-mL centrifuge tubes and cultured with the chondrogenic differentiation medium (Biological Industries, Israel) for 21 days and the medium was refreshed every 3 days. The chondroid pellets were sectioned by a freezing microtome and the slices were stained with toluidine blue in a MSCs Chondro-Staining Kit (XP Biomed Ltd., Shanghai, China) according the instructions [15].…”
Section: Evaluation Of the Differentiation Potential Of Huc-mscsmentioning
confidence: 99%